Experimental investigation on dissociation driving force of methane hydrate in porous media. (15th November 2015) - Li, Shuxia; Xu, Xinhua; Zheng, Ruyi; Chen, Yueming; Hou, Jian
Abstract: As one kind of clean and widely distributed unconventional energy resource, natural gas hydrate (NGH) is attracting increasing attention these years. In this study, the methods of depressurization and thermal stimulation are adopted to dissociate the NGH experimentally, when the initial temperature is 1.0 °C, the initial pressure is 3.1 MPa, the porosity is 0.35 and initial NGH saturation is 32%. The results reveal that during the depressurization process, there exists a pressure difference threshold (Δ P  = 0.19 MPa), and similarly a temperature difference threshold (Δ T  = 1.4 °C) exists during the process of thermal stimulation. NGH will not dissociate until pressure difference or temperature difference outweighs the corresponding threshold value. In addition, the influencing factors of driving force on the gas production performance have been studied. When thermal stimulation is adopted, the driving force of the temperature difference will grow with the increasing hot-brine injection rate and the brine temperature, in which case the gas production rate will drive up. When depressurization is used, the pressure difference driving force will go up with the increasing depressurizing range and depressurizing rate. Driving force is a major factor during NGH dissociation by depressurization and thermal stimulation.